Design and experiment on the air-blowing and vibrating supply seed tray for precision seeder - Zhang, Zhiqiao; Chen, Jin; Li, Yaoming; Guan, Zhuohuai; Liao, Caiqi; Qiao, Xiangshan (International Journal of Agricultural and Biological Engineering, 2022)
Vacuum-vibration precision seeding technology is a crucial technology that affects the industrialization process of super rice plug seedlings. To solve the problems that the vibrating supply seed tray structure in a vacuum-vibration precision seeder caused the vibration of the whole machine and the decline of the seeding eligible rate under high frequency and large amplitude vibration, it is important to design a new supply seed tray structure. This research proposed a method to make the seeds “boiling” under the combined effect of air blowing and vibration, and designed the air-blowing and vibrating supply seed tray structure. FLUENT was used to analyze fluid motion inside the supply seed tray and optimize the structure parameters of the supply seed tray. The maximum airflow velocity was determined when the inlet air pressure was 22 kPa, the number of air inlets was 2, and the diameter of the holes at the bottom of the supply seed tray was 2 mm. Comparative experiments were carried out to prove the air-blowing and vibrating supply seed tray structure could reduce the vibration frequency by 1.5 Hz and decrease the amplitude by 0.25 mm. The mathematical regression models between the inlet air pressure, vibration frequency, amplitude, and seeding performance indexes were established by orthogonal experiments. Through the optimization operation and bench tests, it was determined that when the inlet air pressure was 19.49 kPa, the vibration frequency was 9.00 Hz, and the amplitude was 2.65 mm, the eligible rate, replay rate, and hole rate could reach 93.56%, 3.35%, and 3.09%. The experimental results were generally consistent with the predicted values. The research confirmed that the air-blowing and vibrating supply seed tray could improve the eligible rate while reducing the vibration frequency and amplitude of the vacuum-vibration tray precision seeder. It also provided a necessary basis for precision seeding technology.Keywords: air-blowing and vibrating, precision seeding, FLUENT, orthogonal experimentDOI: 10.25165/j.ijabe.20221503.6873Citation: Zhang Z Q, Chen J, Li Y M, Guan Z H, Liao C Q, Qiao X S. Design and experiment on the air-blowing and vibrating supply seed tray for precision seeders. Int J Agric & Biol Eng, 2022; 15(3): 115–121.